EFEKTIVITAS MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) DILENGKAPI METODE COURSE REVIEW HOREY (CRH) TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA - Hari Pratikno; Sintha Sih Dewanti (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2014)
This study aims to analyze the effectiveness Missouri Mathematics Project (MMP) learning model equipped Course Review Horey (CRH) method compared to MMP learning model and conventional learning model to increase motivation and student learning outcomes. The study was conducted at grade VIII SMP N 3 Godean academic year 2013/2014. This research is a quasi experimental with a pretest-posttest control group design. The population in this study was 192 grade VIII students and divided into 6 classes. The samples of this research are 3 classes, which is the experimental class I, experimental class II and control class. The independent variable in this study are the learning model MMP and CRH method, while the dependent variable are the motivation and student learning outcomes. A questionnaire sheet of motivation scale and pretest-posttest learning outcomes collected the data. Data analysis techniques in this study using ANOVA test, but the previous test that is prerequisite test for normality and homogeneity tests to analyze the scale gain motivation and learning outcomes. The result shows that MMP learning model equipped CRH method is no more effective than the MMP learning model and the conventional model to increase learning motivation, whereas MMP learning model is no more effective than conventional models to increase learning motivation. This can be seen in the ANOVA test sig. 0.978 > 0.05. On learning outcomes, learning model equipped MMP CRH is no more effective method than the MMP learning model and the conventional model to improve learning outcomes. This can be seen in the Tukey test significance value of 0.05, sig. 0.319> 0.05 on the conventional model and sig. 0.456> 0.05 against MMP models. However, MMP learning model is more effective than conventional models to the improvement of learning outcomes. This can be seen in the Tukey test sig. 0.025 <0.05.